Cytogenetic and molecular diagnosis of Fanconi anemia revealed two hidden phenotypes: Disorder of sex development and cerebro‐oculo‐facio‐skeletal syndrome. Issue 7 (23rd May 2019) - Ben Haj Ali, Abir; Amouri, Ahlem; Sayeb, Marwa; Makni, Saloua; Hammami, Wajih; Naouali, Chokri; Dallali, Hamza; Romdhane, Lilia; Bashamboo, Anu; McElreavey, Kenneth; Abdelhak, Sonia; Messaoud, Olfa
Abstract: Background: Several studies have shown a high rate of consanguinity and endogamy in North African populations. As a result, the frequency of autosomal recessive diseases is relatively high in the region with the co‐occurrence of two or more diseases. Methods: We report here on a consanguineous Libyan family whose child was initially diagnosed as presenting Fanconi anemia (FA) with uncommon skeletal deformities. The chromosome breakage test has been performed using mitomycin C (MMC) while molecular analysis was performed by a combined approach of linkage analysis and whole exome sequencing. Results: Cytogenetic analyses showed that the karyotype of the female patient is 46, XY suggesting the diagnosis of a disorder of sex development (DSD). By looking at the genetic etiology of FA and DSD, we have identified p.[Arg798*];[Arg798*] mutation in FANCJ (OMIM #605882) gene responsible for FA and p.[Arg108*];[Arg1497Trp] in EFCAB6 (Gene #64800) gene responsible for DSD. In addition, we have incidentally discovered a novel mutation p.[Gly1372Arg];[Gly1372Arg] in the ERCC6 ( CSB ) (OMIM #609413) gene responsible for COFS that might explain the atypical severe skeletal deformities. Conclusion: The co‐occurrence of clinical and overlapping genetic heterogeneous entities should be taken into consideration for better molecular and genetic counseling. Abstract : This is the first case reported with the combination of three rare entities: Fanconi anemia (FA) associated with disorders of sex development (DSD) and cerebro‐oculo‐facial‐skeletal syndrome (COFS). This article illustrates that the main challenging consequence of comorbidity is the possibility of misdiagnosis especially when phenotypes are extremely rare and overlapping as one phenotype could be hidden by another